An investigation on the effect of central bank money injection on creating currency crisis - Nazi Mohamadzadeh Asl; Leila Jamshidi (Management Science Letters)
This paper investigates the effects of different factors influencing on supplement of currency in Iran and the likelihood of currency crises. The study implements two methods of Logit and Probit to determine the likelihood of currency crises based on the historical data over the period 1989-2012. In this study, currency crisis is defined in terms of three variables of currency change on market, interest rate and central bank foreign deposits. The results of the study indicate that the ratio of government (non-government) liabilities to central bank/Growth domestic product (GDP) has positive (negative) relationship with currency crises.